PRECISION MANAGEMENT IN A CASE OF PHEOCHROMOCYTOMA CATALYSING EARLY DETECTION OF MEDULLARY THYROID CARCINOMA - Devaraja, Vanusha; Nasruddin, Azraai Bahari; Valayutham, Vijaya Mala; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Approximately 35% of pheochromocytoma carry a germline mutation, highlighting the importance of genetic screening in early detection and follow-up of patients with hereditary syndromes. We report a case of a young female in whom individualized pheochromocytoma management expedited the diagnosis of medullary thyroid cancer. CASE A 21-year-old female student presented to the intensive care unit with malignant hypertension complaining of severe headache and abdominal pain. Computed tomography (CT) of the abdomen revealed a heterogenous mass measuring 5.9 x 6.3 x 6.2 cm arising from the left adrenal gland. Plasma free normetanephrines were significantly elevated at 53 nmol/L (normal range: <0.9 nmol/L). She was prepared preoperatively with phenoxybenzamine and propranolol, and successfully underwent open left adrenalectomy. Intraoperative findings revealed a well encapsulated adrenal tumour measuring 7 x 6 cm, weighing 122 grams, confirmed as pheochromocytoma. Genetic testing revealed RET proto-oncogene missense mutation (Cys634Trp). Screening for medullary thyroid carcinoma (MTC) and primary hyperparathyroidism were carried out in order to exclude other possible coexisting disorders in MEN2A syndrome. Serum calcium and parathyroid hormone were normal. Neck ultrasound revealed TIRAD 4 nodules on the upper pole of the right and left thyroid lobe with the largest measuring 1.1 cm and 1.3 cm, respectively. Lymph nodes were not enlarged. Serum calcitonin was elevated at 111 ng/L (normal range: ≤7.6 ng/L). Fine needle aspiration of bilateral thyroid nodules revealed papillary thyroid carcinoma (Bethesda V). She subsequently underwent total thyroidectomy. However, pathological examination of the tumours disclosed low grade multifocal MTC, staining positive for calcitonin, chromogranin A, synaptophysin and CD56. There was no evidence of extrathyroidal tumour extension or lymph node metastasis. The patient was started on replacement L-thyroxine postoperatively. CONCLUSION Early diagnosis of multifocal MTC had been made in this young female due to the benefit of germline mutation. This has reduced the likelihood of unfavorable clinical outcomes associated with MEN2 syndrome.